2005
DOI: 10.1021/tx050231p
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectroscopic Characterization of Protein Modification by Malondialdehyde

Abstract: Malondialdehyde (MDA), a naturally occurring dialdehyde produced in the membrane by lipid peroxidation, is a strong alkylating agent of primary amino groups. We recently raised a monoclonal antibody (mAb1F83) directed to the lipofuscin-like MDA--lysine adduct and demonstrated the presence of immunoreactivity to the antibody in the atherosclerotic lesions, in which intense positivity was associated primarily with macrophage-derived foam cells (Yamada et al., (2001) J. Lipid Res. 42, 1187-1196). To identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…When proteins are treated with MDA, N-propenal (Fig. 1) is the major adduct with very little complex structures formed (37,43,44). If MDHDC is desired in abundance, extra acetaldehyde is needed in modifications (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When proteins are treated with MDA, N-propenal (Fig. 1) is the major adduct with very little complex structures formed (37,43,44). If MDHDC is desired in abundance, extra acetaldehyde is needed in modifications (10).…”
Section: Discussionmentioning
confidence: 99%
“…MDA Modifications-MDA modifications were performed mainly as described previously (35,37). Briefly, BSA (2 mg/ml) was incubated in 100 mM phosphate (pH 7.2) with 1-85 mM MDA in rotation at 37°C for 17 h to produce MDA-BSA.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of precursor peptide was calculated using the ratio of the peak area of precursor peptide of apoA-I from control or modified apoA-I to that of the corresponding 15 N-labeled peptide from 15 N-labeled apoA-I. We focused on Lys residues first, because previous studies identified them as major targets of MDA (24,48). When apoA-I was exposed to a 20-fold molar ratio of MDA for 24 h, isotope dilution revealed that multiple peptides containing one or more Lys residues were lost in high yield.…”
Section: Modification Of Apoa-i By Mda But Not By Four Other Reactivmentioning
confidence: 99%
“…Similar to GA, 4-hydroxy-2-nonenal (HNE) and malondialdehyde (MDA) are among the most common bioactive aldehyde products of oxidative stress (17), whose adducts have been implicated in various immune pathologies (5,18) and linked to induction of adaptive immunity (19,20). Because HNE and MDA attack on proteins can result in RC adduction (21,22), we investigated the significance of such structures and confirm here that RCs are indeed the central immune-active moieties via which these aldehydes modulate Ag immunogenicity. Furthermore, we show that RCs induce a profound Th2 biasing effect regardless of their mode of generation.…”
mentioning
confidence: 99%